Bridging science and decision-making with a storyline-based approach - Laixiang Sun (Cell Reports Sustainability)
Coastal communities face escalating risks from rising seas and stronger storms. In a recent Cell Reports Sustainability article,1 the authors mobilize storylines to evaluate adaptation strategies, focusing on Cyclone Idai’s impact in Beira, Mozambique. Here, we highlight the transformative potential of storylines to inform climate-resilient decision-making.